Next generation probiotics in disease amelioration - Chih‐Jung Chang; Tzu-Lung Lin; Yu‐Ling Tsai; Tsung-Ru Wu; Wei-Fan Lai; Chia‐Chen Lu; Hsin‐Chih Lai (2019)
Studies on the role of gut commensal bacteria in health development have rapidly attracted much more attention beyond the classical pathogens over the last decade. Many important reports have highlighted the changes in the gut microbiota (dysbiosis) are closely related to development of intra- and extra-intestinal, chronic inflammation related diseases such as colitis, obesity/metabolic syndromes, diabetes mellitus, liver diseases, cardiovascular diseases and also cancer and neurodegenerative diseases. To circumvent these difficulties, the strategy of modulating the structure of the gut microbiota has been under intensive study and shed more light on amelioration of these inflammation related diseases. While traditional probiotics generally show marginal ameliorative effects, emerging next generation probiotics start to reveal as new preventive and therapeutic tools. Recent studies have unraveled many potential next generation probiotics (NGP). These include Prevotella copri and Christensenella minuta that control insulin resistance, Parabacteroides goldsteinii, Akkermansia muciniphila and Bacteroides thetaiotaomicron that reverse obesity and insulin resistance, Faecalibacterium prausnitzii that protects mice against intestinal diseases, and Bacteroides fragilis that reduces inflammation and shows anticancer effect. New agents will soon be revealed for targeted therapy on specific inflammation related diseases. The important roles of next generation probiotics and gut microbiota normobiosis on the maintenance of intestinal integrity and homeostasis are emphasized.